2016
DOI: 10.14686/buefad.v5i3.5000195411
|View full text |Cite
|
Sign up to set email alerts
|

Mühendislik Tasarım Temelli Fen Eğitimi ile İlgili Öğretmen Görüşleri

Abstract: Öz: Nitel-durum çalışması olarak yürütülen bu çalışmanın amacı araştırmacılar tarafından yürütülen "Mühendislik Tasarım Temelli Fen Eğitimi (MTTFE) için uygulamalı örnek etkinlikler atölyesi ne gönüllü olarak katılan öğretmenlerin MTTFE hakkındaki görüşlerini ortaya çıkarmaktır. atılımcı görüş formu ile toplanan nitel veriler içerik analizi ile incelenmiştir. Ayrıca bulguları desteklemek amacıyla araştırmacı deneyimlerine de yer verilmiştir. Araştırma sonucunda öğretmenler MTTFE'ye yönelik olumsuz düşünceler b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 10 publications
(20 reference statements)
1
7
0
7
Order By: Relevance
“…Research that suggests the need for teachers and prospective teachers to carry out STEM training indirectly supports the findings of this research (Bozkurt Altan & Ercan, 2016;Hacıoğlu et al, 2016Hacıoğlu et al, , 2017Han et al, 2015;Üçüncüoğlu, 2018;Wang et al, 2011).As a matter of fact, the STEM-focused activities carried out in an RBS which is located in a mountain village were carried out with simple materials, and the positive evaluations made in the students' diaries and the field notes indicate that the application was efficient. It can be stated that the role of the teacher is important for STEMfocused activities towards disadvantaged groups.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Research that suggests the need for teachers and prospective teachers to carry out STEM training indirectly supports the findings of this research (Bozkurt Altan & Ercan, 2016;Hacıoğlu et al, 2016Hacıoğlu et al, , 2017Han et al, 2015;Üçüncüoğlu, 2018;Wang et al, 2011).As a matter of fact, the STEM-focused activities carried out in an RBS which is located in a mountain village were carried out with simple materials, and the positive evaluations made in the students' diaries and the field notes indicate that the application was efficient. It can be stated that the role of the teacher is important for STEMfocused activities towards disadvantaged groups.…”
Section: Discussionsupporting
confidence: 71%
“…Various researchers also reveal the need for teachers and teacher candidates to carry out STEM education (Bozkurt Altan & Ercan, 2016;Hacıoğlu, Yamak & Kavak, 2016Han, Yalvaç, Capraro & Capraro, 2015;Üçüncüoğlu, 2018;Wang, Moore, Roehrig & Park, 2011). In their studies, Bozkurt Altan, and Ercan (2016), Çınar, Pırasa, and Paliç Sadoğlu (2016), Hacıoğlu et al (2016Hacıoğlu et al ( , 2017 and Üçüncüoğlu (2018) reported that as the education and experience of teachers and teacher candidates about STEM education increase, their interest and abilities in this subject will also increase. Kınık Topalsan 2018argued that STEM-educated class teacher candidates perform poorly in creating appropriate problems when developing teaching activities based on engineering design.…”
Section: Socio-economically Disadvantaged Groups Social Justice and mentioning
confidence: 99%
“…In the literature, there are studies carried out with teacher candidates on DBSE applications as well (Bozkurt, 2014;Bozkurt Altan et al, 2016;Capobianco, 2011;Hacıoğlu, 2017;Hacıoğlu, Yamak, & Kavak, 2016;Kınık Topalsan, 2018;Marulcu & Sungur, 2012;Sungur Gül & Marulcu, 2014;Yıldırım, 2018). In these studies, teacher candidates indicated that the design process is based on questioning, makes permanent learning possible and that the big design challenge is motivating (Bozkurt Altan et al, 2016); it was concluded in these studies that DBSE applications develop the scientific creativity and critical thinking (Hacıoğlu, 2017), decision making and scientific process skills of teacher candidates (Bozkurt, 2014) and that although the teacher candidates report some negative views on DBSE, they mostly have positive views and wish to carry out DBSE activities in their lessons (Hacıoğlu et al, 2016).…”
Section: Related Studiesmentioning
confidence: 99%
“…Araştırmalar öğretmen ve öğretmen adaylarının MTS ve BAS uygulamaları konularında pedagojik alan bilgilerinin eksik olduğunu göstermiştir (Dejarnette, 2012). Fakat alınan eğitimler, yapılan uygulamalar öğretmenlerin mühendislik tasarım temelli etkinlikleri uygulama konusuna olumlu bakmalarını ve bu konuda istekli davranmalarını sağlayabilir (Hacıoğlu, Yamak ve Kavak, 2016).…”
Section: Sonuç Ve öNeri̇lerunclassified